E.A. Bennet correspondence - Bennet, E. A. (Edward Armstrong)
TLS (5 January 1972) from Bennet to K.R. Eissler summarizing Bennet's conversations with C.G. Jung concerning Sigmund Freud's relationship with his wife, Martha, and sister-in-law, Minna Bernays. Includes letters to Bennet from Pierre Janet (in French) and from Wilhelm Stekel.
In part, photocopies.
Psychiatrist. Born 1888; died 1977.
Collection material in English and French.
Forms part of: Sigmund Freud collection.
Keywords: Bernays, Minna -- Family; Eissler, K. R. -- 1908-1999 -- Correspondence; Freud, Martha, -- 1861-1951 -- Family; Freud, Sigmund, -- 1856-1939 -- Family; Janet, Pierre, -- 1859-1947 -- Correspondence; Jung, C. G. -- 1875-1961.; Stekel, Wilhelm, -- 1868-1940 -- Correspondence; Freud family; Psychiatrists